Method for in-situ balancing of rotatives by use of an on-the-fly pulsating material removal process - Stoesslein, Moritz (2016)
Balancing rotating systems is a challenging task, which requires (dis)assembly of the system to enable mass adjustments; thus the development of a method to balance rotatives in-situ (i.e. without disassembly) using pulsed laser ablation (PLA) is a key technology enabler. PLA for in-situ balancing offers inherent advantages of an adjustable frequency (to match that of the rotating part) and variable pulse energy (to control the mass removal).